EFFECTIVENESS OF DIALECTICAL BEHAVIOR THERAPY (DBT) IN DEALING WITH SUICIDE ATTEMPTS: EFEKTIVITAS DIALECTICAL BEHAVIOR THERAPY (DBT) DALAM MENANGANI PERCOBAAN BUNUH DIRI - Mufidetul Hasanah; Ananta Yudiarso (SOSIOEDUKASI, 2025)
Suicide attempts are a parameter of the signs of someone wanting to suicide. One of the causes of individuals attempting suicide is psychological problems, one of which is borderline personality disorder. One intervention that can be used in dealing with suicide attempts in patients is dialectical behavior therapy (DBT). Researchers found inconsistencies in the effectiveness of DBT in dealing with suicide attempts. This made the researchers test the effect size of DBT interventions on suicide attempts using the meta-analysis method, so the purpose of this study was to increase statistical power in the analysis of dialectical behavior therapy (DBT) on suicide attempts. The results of this study showed that the effect of DBT intervention in dealing with suicide attempts was in the low category, -0.141. Several causes of low effect size have been explained in this study, one of which is the influence of variables outside the study that cannot be controlled (noise), thus causing a low effect size. The implication of this study is that insufficiently specific participant criteria can affect DBT interventions in dealing with suicide attempt behavior.